2012
DOI: 10.1188/12.onf.e499-e510
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Illness Trajectory Framework to Describe the Work of Transitional Cancer Survivorship

Abstract: Purpose/Objectives Although frameworks for understanding survivorship continue to evolve, most are abstract and do not address the complex context of survivors’ transition following treatment completion. The purpose of this theory adaptation was to examine and refine the Illness Trajectory Theory, which describes the work of managing chronic illness, to address transitional cancer survivorship. Data Sources CINAHL, PubMed, and relevant Institute of Medicine reports were searched for survivors’ experiences du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 105 publications
0
20
0
Order By: Relevance
“…4,12,[22][23][24]27 Fear of recurrence represents existential concerns, uncertainty related to prognosis, and perceived morbidity associated with advanced disease. Anxiety is closely related to fear of recurrence and follow-up surveillance visits but lack of adequate knowledge to manage symptoms, uncertainty about the predicted recovery trajectory, and information and access to resources will increase a woman's anxiety levels.…”
Section: Breast Cancer Survivor Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12,[22][23][24]27 Fear of recurrence represents existential concerns, uncertainty related to prognosis, and perceived morbidity associated with advanced disease. Anxiety is closely related to fear of recurrence and follow-up surveillance visits but lack of adequate knowledge to manage symptoms, uncertainty about the predicted recovery trajectory, and information and access to resources will increase a woman's anxiety levels.…”
Section: Breast Cancer Survivor Needsmentioning
confidence: 99%
“…19,21 The expectations for health care providers in survivorship care have been delineated, but to improve health and QOL outcomes for survivors, it is equally important to engage, inform, and support BCS in the transitional survivorship work in the context of their everyday lives. 22,23 The purpose of this article is to review reported concerns and needs of BCS in the transitional phase of survivorship, from curative intent therapy, and describe approaches to quality patient-centered BCS care.…”
mentioning
confidence: 99%
“…The stage of awareness in the initial year of the transition to survivorship also reflects a time of changing relationships (Bennion & Molassiotis, 2013). Diminishing social support is experienced from family and friends, contact with healthcare providers is dramatically reduced, and issues related to body image and sexuality begin to emerge, often affecting partner relationships (Allen, Savadatti, & Levy, 2009;Bennion & Molassiotis, 2013;Dow & Lafferty, 2000;Klimmek & Wenzel, 2012;Lethborg et al, 2000;Manne et al, 2006).…”
Section: Developing Awarenessmentioning
confidence: 97%
“…The process of recovery after therapy and transitioning to survivorship requires work (Klimmek & Wenzel, 2012). The majority of patients will cope with the challenges of getting this work done and move on as cancer survivors, often with a positive Note.…”
Section: Developing Awarenessmentioning
confidence: 97%
See 1 more Smart Citation